The Utilization of Infographic-Based Learning Media to Increase Students' Interest in Learning - Ade Taufiq Khaeranda; Hamsi Mansur; Agus Salim (Publikasi Indonesia, 2024)
Technological developments have had a major impact on education, especially in increasing the effectiveness of the learning process. Infographics are one of the innovative and technology-based learning media, which combines information with interesting visual elements. This study analyzes various literature to examine the influence of the use of infographics in learning on students' learning interests. The results of the study show that infographics can increase students' interest in learning by presenting information visually, making it easier to understand, and making the material more interesting. Infographics also help students remember information, increase engagement, and support independent learning. In addition, infographics are easily accessible and shared digitally, making it easier for students to repeat the material. Research shows that students are more focused and motivated when using visual media compared to conventional lecture methods. Therefore, the use of infographics as a medium of learning can be used as an effective strategy for overcoming various obstacles in learning activities and resulting in an improvement in the quality of education. Educators are advised to utilize infographics in their learning strategies to achieve more optimal results. In conclusion, infographics are an effective tool to make learning more interactive and interesting and to increase students' interest in learning.